Discovering Computers 98: A Link to the Future - Shelly, Gary B. and Thomas J. Cashman, Gloria A. Wa. (Cambridge Course Technology, 1998)
Discovering Computers 98: A Link to the Future, World Wide Web Enhanced is intended for use in a one-quater or one-semester introductory computer course. No experience with computer is assumed. The material presented provides the most in-depth treatment of introdactory computer subject ever found in a textbook. Students will finish the course with a complete understanding of computers, how to use computers, and how to access information on the World Wide Web.
Keywords: Teaching English